Low Molecular Weight Dextran Infusions in Systemic Sclerosis with Raynaud's Phenomenon: A Report of Nine Cases. Issue 5736 (12th December 1970) - Lane, Peter
Abstract : Two litres of low molecular weight dextran in normal saline were given intravenously over 48 hours to 10 patients with systemic sclerosis and Raynaud's phenomenon. The finger temperatures of nine were recorded under standardized conditions. One patient had lowered temperatures of the fingers, two had a rise in temperature, and six had no change. There were no side effects of the treatment. None of the 10 patients showed any clinical improvement.